Problematika Evaluasi Pembelajaran Pendidikan Agama Islam di Era Merdeka Belajar pada di SDN 073 Pajagalan Bandung - Syifa Syakira Salma; Nurulaini Wulandari; Andriansyah Putra; Muhsin (Jurnal Dirosah Islamiyah, 2025)
This study is motivated by the ongoing challenges in evaluating Islamic Religious Education (IRE) learning, particularly within the context of the implementation of the Merdeka Curriculum. The research aims to examine the obstacles and issues in the evaluation process of IRE learning at SDN 073 Pajagalan, Bandung. A qualitative approach with a descriptive method was employed, using data collection techniques such as observation, interviews, and documentation. The findings indicate that the evaluation of IRE learning has been aligned with the Merdeka Curriculum, which emphasizes a holistic approach covering cognitive, affective, and psychomotor domains. However, in practice, teachers face several challenges, including limited face-to-face instructional time (only once a week), high administrative workload, limited technological proficiency, and the diverse backgrounds of students. Teachers attempt to overcome these challenges by innovating evaluation methods, utilizing technology such as WhatsApp and Google Forms, and implementing relevant formative and summative assessments. Furthermore, collaboration with parents and learning communities plays a crucial role in supporting effective evaluation. The study concludes that despite various challenges, the implementation of IRE learning evaluation at SDN 073 Pajagalan Bandung generally aligns with the principles of the Merdeka Curriculum, focusing on the holistic development of students' character and competencies.